PENGARUH GAYA KEPEMIMPINAN MANAJER DAN MONITORING CONTROL TERHADAP ESKALASI KOMITMEN DALAM PENGAMBILAN KEPUTUSAN PERSETUJUAN PENGAJUAN KREDIT SEPEDA MOTOR (Studi Kasus Pada PT Delta Abadisentosa) - Rakhmi Ridhawati; Ferra Maryana; Aidina Fitriana (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2018)
Abstrack, This research aimed to give empirical evidence about the Manager Style of Leadership and Monitoring of Control To Escalation of Commitment In Decision Making Of Motorbike Credit Approved (Case Study at PT.DELTA Abadisentosa). Population in this research were manager of PT. Delta of Abadisentosa Kalsel - Teng counted 47 people as samples. The Result give empirical evidenced that the manager style of leadership and monitoring of control have an effect to escalation of commitment in decision making of motorbike credit approved either partial or simultan.